2019
DOI: 10.1088/1402-4896/ab3838
|View full text |Cite
|
Sign up to set email alerts
|

62 nm CW wavelength-selectable erbium-doped fiber compound-ring laser with stable single-mode output

Abstract: In this demonstration, an erbium-doped fiber (EDF) based laser with stable, wide and wavelength-selectable single-longitudinal-mode (SLM) performances is designed and demonstrated. Here, to achieve SLM oscillation, a compound-ring scheme is constructed in the EDF laser cavity serving as a mode-restriction-filter for densely side-mode suppression. Moreover, the continuous-wave tunability can be scaled from 1520.0 to 1582.0 nm by using the proposed compound-ring scheme and commercial C-band EDF amplifier. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Then, to understand the output stabilities of the presented EDF laser, the fluctuations of power and wavelength can be observed through a period of observation time. Figures 3(a Next, a delayed self-homodyne technique could be applied to implement the SLM performance for each lasing single wavelength [17]. The experimental setup is illustrated in figure 4.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, to understand the output stabilities of the presented EDF laser, the fluctuations of power and wavelength can be observed through a period of observation time. Figures 3(a Next, a delayed self-homodyne technique could be applied to implement the SLM performance for each lasing single wavelength [17]. The experimental setup is illustrated in figure 4.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…However, owing to the longer fiber cavity and homogeneous broadening influence [12], achieving a stable multi-wavelength operation with single-longitudinal-mode (SLM) output is difficult. Therefore, the Rayleigh backscattering (RB) effect [13], EDF-based saturable absorber (SA) [14], MZI scheme [15], optical injection technique [16] and compoundfiber-ring structure [17] have been investigated to suppress the multi-longitudinal-mode (MLM) oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…The previous EDF compound-ring laser configurations could achieve single or dual-wavelength SLM output within the C-band operation range [10,11,[31][32][33][34]. The prior result indicated that the output wavelength power was smaller and dropped on both sides slightly.…”
Section: Introductionmentioning
confidence: 95%
“…The prior result indicated that the output wavelength power was smaller and dropped on both sides slightly. Moreover, exploiting a triple-ring scheme in EDF based laser could reach the SLM operation [31][32][33][34], while the length difference of each fiber ring was larger to cause a wide FSR for multi-mode suppression. Even if the previous studies could extend the tunability, the observed output power could not achieve a flat distribution over the whole tuning range.…”
Section: Introductionmentioning
confidence: 99%